Artificial Intelligence in Laryngeal Endoscopy Künstliche Intelligenz in der laryngealen Endoskopie - Kist, Andreas (Sprache, Stimme, Gehör, 2023)
The application of artificial intelligence (AI) in medical imaging allows the rapid and complex analysis of endoscopic image material. Laryngeal endoscopy has several applications with its variants, such as video stroboscopy and high-speed video endoscopy. AI can enhance image quality, detect lesions through object detection, and quantify vocal fold vibration behavior through glottal area identification. The application of AI-assisted endoscopy systems simplifies diagnosis and therapy monitoring and supports the medical staff in their tasks.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Artificial intelligence; laryngeal endoscopy; medical imaging